Kidney tubule health, mineral metabolism and adverse events in persons with CKD in SPRINT. Issue 9 (2nd September 2021) - Ascher, Simon B; Scherzer, Rebecca; Estrella, Michelle M; Berry, Jarett D; de Lemos, James A; Jotwani, Vasantha K; Garimella, Pranav S; Malhotra, Rakesh; Bullen, Alexander L; Katz, Ronit; Ambrosius, Walter T; Cheung, Alfred K; et al.
Abstract: Background: Measures of kidney tubule health are risk markers for acute kidney injury (AKI) in persons with chronic kidney disease (CKD) during hypertension treatment, but their associations with other adverse events (AEs) are unknown. Methods: Among 2377 Systolic Blood Pressure Intervention Trial (SPRINT) participants with CKD, we measured at baseline eight urine biomarkers of kidney tubule health and two serum biomarkers of mineral metabolism pathways that act on the kidney tubules. Cox proportional hazards models were used to evaluate biomarker associations with risk of a composite of pre-specified serious AEs (hypotension, syncope, electrolyte abnormalities, AKI, bradycardia and injurious falls) and outpatient AEs (hyperkalemia and hypokalemia). Results: At baseline, the mean age was 73 ± 9 years and mean estimated glomerular filtration rate (eGFR) was 46 ± 11 mL/min/1.73 m 2 . During a median follow-up of 3.8 years, 716 (30%) participants experienced the composite AE. Higher urine interleukin-18, kidney injury molecule-1, neutrophil gelatinase-associated lipocalin (NGAL) and monocyte chemoattractant protein-1 (MCP-1), lower urine uromodulin (UMOD) and higher serum fibroblast growth factor-23 were individually associated with higher risk of the composite AE outcome in multivariable-adjusted models including eGFR and albuminuria. When modeling biomarkers in combination, higher NGAL [hazard ratio (HR) = 1.08 per 2-fold higher biomarker level, 95% confidence interval (CI) 1.03–1.13], higher MCP-1 (HR = 1.11, 95% CI 1.03–1.19) and lower UMOD (HR = 0.91, 95% CI 0.85–0.97) were each associated with higher composite AE risk. Biomarker associations did not vary by intervention arm (P > 0.10 for all interactions). Conclusions: Among persons with CKD, several kidney tubule biomarkers are associated with higher risk of AEs during hypertension treatment, independent of eGFR and albuminuria.